BEBAN KERJA DAN KESEIMBANGAN KEHIDUPAN KERJA TERHADAP KEPUASAN PEKERJAAN KARYAWAN: PERAN MEDIASI KECERDASAN KESULITAN (ADVERSITY QUOTIENT) SEBUAH STUDI DI BMT UGT SIDOGIRI CENTER - Bailatus Saidah; Zaim Mukaffi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effect of workload and work-life balance on employee job satisfaction, with adversity quotient as a mediating variable. The research is grounded in the Job Demands-Resources (JD-R) model, which explains how job demands, job resources, and personal resources shape employees’ work outcomes. A quantitative explanatory approach was employed, involving all 70 employees of BMT UGT Sidogiri Pusat as research respondents using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that workload and work-life balance do not have a significant direct effect on employee job satisfaction. However, adversity quotient significantly mediates the relationship between workload and job satisfaction, while it does not mediate the relationship between work-life balance and job satisfaction. These results suggest that employee job satisfaction is not solely determined by working conditions, but is also influenced by individual psychological resilience in coping with work demands. This study highlights the importance of strengthening employees’ adversity quotient as a personal resource to maintain job satisfaction, particularly in organizations with high job demands such as Islamic microfinance institutions